Bricked Subwavelength Gratings: A Tailorable On‐Chip Metamaterial Topology. Issue 6 (2nd May 2021) - Luque‐González, José Manuel; Ortega‐Moñux, Alejandro; Halir, Robert; Schmid, Jens H.; Cheben, Pavel; Molina‐Fernández, Íñigo; Wangüemert‐Pérez, J. Gonzalo
Abstract: Integrated metamaterials are redefining the capabilities of silicon photonic chips. In providing lithographic control over dielectric permittivity, dispersion and anisotropy, they are enabling photonic devices with unprecedented performance. However, the implementation of these materials at telecom wavelengths often requires a fabrication resolution of the order of 100 nm and below, pushing current wafer‐scale fabrication technology to its limits and hindering the widespread exploitation of on‐chip metamaterials. Herein, a subwavelength grating metamaterial with bricked topology is proposed, that provides lithographic control over the metamaterial dispersion and anisotropy using a single etch Manhattan‐like geometry with pixel dimensions up to 150 × 150 nm 2, thereby easing the path toward fabrication at wafer‐scale. The behavior of these structures as biaxial crystals is analytically shown, validating their use in high performance on‐chip beam‐splitters. Through engineering of the metamaterial anisotropy tensor, the splitters are shown to exhibit sub‐decibel insertion losses and imbalance over a 400 nm design bandwidth, via 3D FDTD simulations. The excellent device performance is demonstrated over a 140 nm bandwidth, limited by the measurement setup. Abstract : A novel subwavelength grating (SWG) topology that provides lithographic control over the metamaterial dispersion and anisotropy with a single etch Manhattan‐like geometry is proposed. This topology, allows larger dimensions compared with conventional SWG, easing the path toward wafer‐scale fabrication. Based on this metamaterial, two multimode mode interferometers are shown, exhibiting sub‐decibel insertion losses and imbalance over a 400 nm bandwidth.